Controlled Assembly of Liquid Metal Inclusions as a General Approach for Multifunctional Composites. Issue 46 (12th October 2020) - Ford, Michael J.; Patel, Dinesh K.; Pan, Chengfeng; Bergbreiter, Sarah; Majidi, Carmel
Abstract: Soft composites that use droplets of gallium‐based liquid metal (LM) as the dispersion phase have the potential for transformative impact in multifunctional material engineering. However, it is unclear whether percolation pathways of LM can support high electrical conductivity in a wide range of matrix materials. This issue is addressed through an approach to LM composite synthesis that focuses on the interrelated effects of matrix curing/solidification and droplet formation. The combined influence of LM concentration, particle size, and sedimentation is explored. By developing this approach, the functionalities that have been demonstrated with LM composites can be generalized to other matrix materials that impart additional functionality. Specifically, composites are synthesized using a biodegradable/reprocessable plastic (polycaprolactone), a hydrogel (poly(vinyl alcohol)), and a processable rubber (a styrene–ethylene–butylene–styrene derivative) to demonstrate wide applicability. This method enables synthesis of composites: i) with high stretchability and negligible electromechanical coupling (> 600% strain); ii) with Joule‐heated healing and reprocessability; iii) with electrical and mechanical self‐healing; and iv) that can be printed. This approach to controlled assembly represents a widely applicable technique for creating new classes of LM composites with unprecedented multifunctionality. Abstract : A general approach to synthesize soft material composites that incorporate liquid metal is described. The approach extends functionalities imparted by liquid metal inclusions to functional matrix materials. A key to this study is the understanding of the influence of processing parameters to activate electrical conductivity in the composites.